Embryonic Vascular Dysgenesis: The Origin of Proximal Femoral Focal Deficiency - Hootnick, David R; Vargesson, Neil; Horton, Jason A; Chomiak, Jiri (Birth defects research, 2025)
BACKGROUND: Proximal Femoral Focal Deficiency (PFFD) is the most proximal manifestation of a syndrome involving Congenitally Shortened lower Limbs (CSL), which also affects the fibula and midline metatarsals. This pattern of congenital human long bone deficiencies corresponds, in a time dependent manner, to the failed ingrowth pathways of new blood vessels of the growing embryonic limb. The distal femoral condyles are, in contrast, served by an alternative vascular supply from around the knee joint, and so remain resistant to the CSL deficiency. AIM: We hypothesize that embryonic vascular dysgenesis causes PFFD, as well as the cardinal features of the Femoral, Fibular and midline Metatarsal deficiencies (FFM) syndrome. RESULTS: Arteriography of CSL with PFFD reveals diminution or failed formation of the Femoral Artery (FA), which corresponds to downstream skeletal reductions. It may also reveal preservation of the primitive Axial Artery (AA) of the embryonic limb. The combination of missing and retained primitive vessels inform the time, place, and nature of the etiologic vascular events. This suggests that PFFD is the visible expression of a normally prefigured cartilaginous scaffold of the femur, which develops in conformity with the available pattern of blood vessels present. The teratogen thalidomide, known to affect the forming embryonic vasculature, also produces PFFD indistinguishable from the naturally occurring entity. CONCLUSION: The entire spectrum of PFFD, including phocomelia, fibular, and metatarsal dystrophisms, should thus be regarded as downstream skeletal results of embryonic arterial dysgeneses.
Keywords: arteria femoralis; vascular patterning; Femur; femoral, fibular, and midline metatarsal deficiencies (FFM); Femoral Artery; fibula; phocomelia; vrozené deformity dolní končetiny; dystrophisms; limb differences; Fibula; lidé; Humans; proximal femoral focal deficiency (PFFD); Metatarsal Bones; congenitally shortened lower limbs (CSL); femur; thalidomide; Lower Extremity Deformities, Congenital; metatarzální kosti